Warisan Budaya Pantun dalam Manuskrip Surat Incung - Sunliensyar, Hafiful Hadi (Manuskripta, 2022)
Pantun is one of the ancient poetry that is the cultural heritage of the society in the archipelago. At first, the Pantun tradition is an oral tradition that functioned for various purposes. However, Pantuns are also transformed into written form after. The text entity of the Pantun is inserted in various Hikayat Melayu and in local literary manuscripts, such as the Ulu manuscript and the Incung Kerinci manuscript. This study aims to identify Pantuns in the Incung manuscripts that have been translated. The result of this research shows that 14 Incung manuscripts containing the texts of Pantun. Its texts are categorized as “pantun biasa” dan “talibun” with distinctive characteristics. Its specific character is the existence of an interjection or a sentence containing interjection between the “sampiran” and “isi”. The availability of pantuns is only found in the Incung manuscript containing the prose of lamentations. The function of pantuns is as a "sweetener" element and adds poetic value in the Incung prose. the content of pantun always has a correlation with the mood expressed by the manuscript writer. === Pantun merupakan salah satu karya sastra lama yang menjadi warisan budaya masyarakat di Kepulauan Nusantara. Tradisi pantun pada dasarnya adalah tradisi lisan yang difungsikan untuk berbagai tujuan. Namun demikian, pantun juga ditransformasikan dalam bentuk tulisan. Wujud teks pantun disisipkan dalam berbagai hikayat Melayu dan di dalam manuskrip kesusastraan lokal seperti dalam manuskrip Ulu dan manuskrip Incung Kerinci. Penelitian ini bertujuan mengidentifikasi teks-teks pantun dalam manuskrip Incung yang telah dialihaksarakan. Hasilnya menunjukkan bahwa terdapat 14 manuskrip Incung yang memuat teks pantun. Teks pantun tersebut adalah pantun biasa dan talibun dengan karakteristik yang khas. Kekhasan tersebut adalah adanya interjeksi atau kalimat mengandung interjeksi di antara sampiran dan isi. Keberadaan pantun hanya terdapat pada manuskrip Incung yang berisi prosa ratap-tangis. Fungsi pantun adalah sebagai unsur “pemanis” dan penguat nilai puitis dalam sastra Incung. Isinya selalu berelasi dengan suasana hati yang diungkapkan oleh penulis manuskrip.